IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) SEBAGAI PEMBENTUK PENDIDIKAN BERKARAKTER - Wandasari, Yulisa (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at investigating the implementation of school literacy movement (GLS) as a character of educational formation. This research was qualitative that produces descriptive data in the form of words written or spoken of people and observed behavior. While, the type of research was a case study. Data collection techniques used were observation and interviews. The results of the research were school literacy movement was able to access, understand, and use through reading. Implementation of the school literacy movement in SMK Negeri 1 Tanah Abang run well by involving the school community (learners, teachers, principals, education personnel, school supervisors, school committee, parents of learners), and stakeholders under the coordination of the Directorate General Primary and Secondary Education Ministry of Education and Culture.